Development of mobile application based on analysis of factors affecting bra selection - Shahood Uz Zaman; Aqsa Imran; Babar Ramzan (Journal of Engineered Fibers and Fabrics)
Selection of the right size and comfortable bra is very important as the wrong bra selection may lead to many problems like skin irritation, pain, and in extreme cases can induce breast cancer. This study consists of two phases, in the first phase a survey was conducted to investigate factors affecting wrong bra selection leading to health problems, in the second phase a mobile application “Bra Guide” was developed to create awareness in women related to health issues, extraction of breast measurement, and bra sizing system. The collected data was analyzed with factor analysis using SPSS, IBM AMOS 26.0, and the mobile application was developed by using the Flutter framework. Results showed that 84% of women don’t have awareness related to bra sizing system and they also fall behind with bra style feature knowledge. The second most important factor is the nonexistence of bra fitting services which causes most women to use ill-fitted bras for their complete life, furthermore, 79% of women wear bras 24 h a day which causes health issues. A mobile application “Bra Guide” has been developed which helped in delivering awareness and solutions regarding bra size, style, and breast health issues as 91.2% of respondents rated this application as highly satisfied.